Long-Term Outcomes of External Dacryocystorhinostomy in the Age of Transcanalicular Microendoscopic Techniques - M. Alnawaiseh; N. Mihailovic; A. C. Wieneke; V. Prokosch; A. Rosentreter; R. L. Merté; N. Eter (Journal of Ophthalmology)
Purpose. This study aimed to evaluate long-term results of external dacryocystorhinostomy (DCR) at a tertiary eye care center specializing in lacrimal duct surgery in Germany. Methods. The medical records of 1010 patients with acquired nasolacrimal duct obstruction (NLDO), who had undergone lacrimal duct surgery at a tertiary eye care center, were reviewed. Only adult patients who had undergone external DCR were included. The evaluation included the following parameters: age, gender, duration of symptoms, patient satisfaction, previous dacryocystitis, complication rates, and surgical outcome. Results. 154 eyes of 146 patients (14.5%) could be included in the study. The average age was 64.1±29.7 years. 66.4% of patients were females and 33.6% were males. Acute or chronic dacryocystitis was found in 81 patients (55.5%). Overall, 82.8% of patients had full resolution of symptoms. The success rate of external DCR for patients with previous episodes of dacryocystitis was 82.7% compared to 83.4% for patients without dacryocystitis in their medical history. Conclusion. In cases in which transcanalicular microendoscopic techniques are contraindicated (e.g., after dacryocystitis) or in complex cases where microendoscopic procedures have failed (revision surgery), external DCR is still the surgical treatment of choice with very good postoperative success.